The Churchmanship of Samuel Wilberforce - Newsome, D. H. (Studies in church history, 1966)
Do you remember the Very Reverend Dr Brownside in Newman’s Loss and Gain?As a divine, he seemed never to have had any difficulty on any subject; he was so clear or so shallow that he saw to the bottom of all his thoughts. ... He was a popular preacher; that is, though he had few followers, he had numerous hearers.We may grant that Newman did not intentionally malign his former friends and enemies. To hint as much would be, as he himself assured James Stephen, ‘to act the part of the good lady in the Spectator, who turned The Whole Duty of Man into a manual of personal slander’. And if the image of Samuel Wilberforce flashed through Newman’s mind as he drew this caricature—though it is mere surmise that it did—then undoubtedly he covered up the mischievous thought by endowing Dr Brown-side with a physical frame and a particular brand of theological ineptitude as far removed as possible from the actual appearance and acknowledged teaching of the celebrated bishop of Oxford.